ANALISIS KUALITAS PELAYANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MAHAKAM ULU - Cin, Muksin; Irawan, Bambang; Susilo Utomo, Heryono (Magister Administrasi Publik FISIP Universitas Mulawarman, 2023)
The purpose of this study is to describe the quality of population and civil registration services in Mahakam Ulu Regency and to identify and analyze what are the supporting and hindering factors. The approach in this research is descriptive qualitative to get a clearer picture of the phenomena that occur in relation to the problem under study. The data analysis technique used is interactive model analysis. The results showed that the quality of service at the Department of Population and Civil Registration of Mahakam Ulu Regency was good, it could be seen in the Tangibles dimension (direct evidence) which was quite adequate, in addition to the Reliability dimension, it was also good because of the ability of officers to provide services. Already well. Then the Responsiveness dimension has also been carried out swiftly in providing services. Meanwhile, the Assurance dimension is carried out by providing assurance that all service products can be completed properly. Finally, the Empathy dimension is carried out by preparing a complaint service to help the community with something they do not know.